Conentrating Of Phosphate With Simultaneous Removal Of Sodium Chloride Via Nanofiltration - Vengedesweren, Durgashene (Universiti Sains Malaysia, 2021)
Recovery of phosphorus has been gaining importance due to its natural scarcity and high economical value. Aquaculture and poultry effluent with significant phosphate content required further treatment before discharging to the environment. However, its trace quantity makes the whole process not feasible. Moreover, the presence of salt (NaCl) makes the effort to recover the phosphate as fertilizer less attractive due to its unwanted salinity. In this study. nanofiltration had been tested to recover/concentrate the phosphate ions and at the same time removing the sodium chloride. The study was conducted using Desal DK5 membrane in dead-end mode using Dead End Stirred Cell at different pressures and concentration to investigate the effect of transmembrane pressure (TMP) and feed concentration on the rejection of phosphate ions, average permeate flux and concentrating factor. The highest phosphate ion rejection, 99.86%, was achieved at the lowest pressure, 2 bar, and lowest concentration of potassium dihydrogen phosphate solution (20 ppm). However, in the same parameter, the permeate flux and the concentrating factor (CF) obtained were the lowest compared to other sets of experiment which are 20.15 L/m2.h and 1.55 respectively. The maximum CF of could be achieved at 6 bar. The removal of NaCl increases with pressure, however the presence of NaCl further reduce the phosphate ion rejection, lowering the average permeate flux and concentrating factor. The results obtained is very promising in terms of harvesting the nutrient from aquaculture effluent and at the same time removing the unwanted salinity.